2001
DOI: 10.1007/bf03168823
|View full text |Cite
|
Sign up to set email alerts
|

Premature hair greying may predict reduced bone mineral density in Graves’ disease

Abstract: Premature greying may be a weak marker for reduced BMD in women with a history of Graves' disease, but it is not a marker in normal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Similar findings are also reported by Orr‐Walker et al, 73 In graves' disease patients, Leary et al, reported that Mean Z and T scores at the lumbar spine were significantly lower in subjects with PGH compared to control group. PGH was present in 36% of patients with Graves' patients, compared to only 25% of control women 74 . On the contrary, the “Rancho Bernardo Study”, (n = 1207) did not find any significant association between PGH and osteopenia in either men or women 32 .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Similar findings are also reported by Orr‐Walker et al, 73 In graves' disease patients, Leary et al, reported that Mean Z and T scores at the lumbar spine were significantly lower in subjects with PGH compared to control group. PGH was present in 36% of patients with Graves' patients, compared to only 25% of control women 74 . On the contrary, the “Rancho Bernardo Study”, (n = 1207) did not find any significant association between PGH and osteopenia in either men or women 32 .…”
Section: Resultsmentioning
confidence: 86%
“…under the age 50. 43,59 Other potential comorbid conditions are altered thyroid function, 37,53,77 hyperuricemia, 28 altered liver function, 1,28 osteopenia, 22,32,[73][74][75] hearing loss, 30,34 psoriasis, 23 etc.…”
Section: Discussionmentioning
confidence: 99%
“…Premature greying may be a weak marker for reduced bone mineral density (BMD) in women with a history of Graves' disease, but it is not a marker in normal women [33]. But later studies showed no such link [34].…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…Isolated cases with hair color changes in association with other diseases/syndromes have been reported. Decreased production of the melanin pigment causes hair to become lighter, which was found in several medical conditions affecting hair color, such as coronary artery disease, osteopenia, and Graves disease [Eisenstein and Edelstein, 1982; Rosen et al, 1994; Leary et al, 2001]. We therefore suggested that a temporary reduction of melanin production in the fetal, but not infancy, stage through an undiscovered mechanism due to GNPTAB defects may cause the hair color change in the early infancy as observed in our patient.…”
Section: To the Editormentioning
confidence: 99%